Beyond professional terms – the family metaphor in staff descriptions of their relations to young people in secure - Peter Andersson; Marie Sallnäs (Scottish Journal of Residential Child Care, 2024)
One premise for the organisation of residential care for youth is that staff are expected to relate to each young person individually, but also to the group of young people as a whole. The relational interplay between staff and placed youths in secure unit care is fundamentally based on asymmetry, with interactions taking place in a context of confinement. The aim here is to explore how staff working in secure institutional care for youths in Sweden understand and describe their relationships with youth in terms that extend beyond professionalism, and especially their use of the family metaphor. Fifty-three interviews with staff were analysed in a two-step qualitative analysis, which generated three themes that highlighted staff narratives focusing on descriptions of parenting, sibling relationships, and closeness without using the family metaphor. One conclusion is that despite an overall shift away from the family metaphor, in the direction of framing residential care in professional terms, the family concept seems to sit quite well even in an environment with ambitions to provide professional care. The family metaphor may not be the cornerstone of care, but it is eminently present.